A Novel De Novo EFNB1 Gene Mutation in a Mexican Patient with Craniofrontonasal Syndrome - M. A. Ramirez-Garcia; O. F. Chacon-Camacho; C. Leyva-Hernandez; A. Cardenas-Conejo; J. C. Zenteno (Case Reports in Genetics)
Craniofrontonasal syndrome (CNFS) is an X-linked disorder caused by mutations in the EFNB1 gene in which, paradoxically, heterozygous females are more severely affected than hemizygous males. In this paper, the clinical and molecular studies of a female subject with CFNS are described. A novel de novo c.473T>C (p.M158T) mutation in exon 3 of EFNB1 was demonstrated in this patient. The M158 residue of the Ephrin-B1 protein is highly conserved between species. Our results expand the mutational spectrum exposed by CNFS.